Manufacturing and Measuring Techniques for Graphene-Silicone-Based Strain Sensors (2023)
The development of techniques for synthesizing graphene and its derivatives, as well as currently available nanocomposite fabrication techniques, coupled with the diverse applications of strain and pressure sensors, has made this field of growing interest in the last decade. This article provides an overview of conventional strain sensor manufacturing techniques, such as in situ polymerization, solution blending, and electrospinning. It also covers various additive manufacturing techniques such as vat-photopolymerization, material extrusion, material jetting, sheet lamination, and the most common graphene synthesis techniques like chemical-based, vapor deposition, exfoliation, and mechanical-based methods. The review is also completed with a discussion about the sensing mechanisms of strain sensors, considering the various process parameters to characterize and compare the performance of a strain sensor. Finally, we examine several key aspects of the sensor’s component materials, the type of sensing mechanism, and the appropriate manufacturing process. © 2022, The Minerals, Metals & Materials Society.